ASSESSMENT OF HEAT TRANSFER IN FUEL CHANNEL OF INDIAN PHWR UNDER POSTULATED LARGE BREAK LOSS OF COOLANT ACCIDENT: EXPERIMENTAL AND NUMERICAL STUDY - Ajay Ketan; Kumar Ravi; Gupta Akhilesh (EPJ Web of Conferences, 2021)
The behaviour of the channel under postulated large break LOCA scenario had been a prime safety concern. The radiative heat transfer is predominant in a channel when the convective cooling environment is marred. The estimation of temperature distribution in the fuel pins at elevated temperature is essential from the point of view of hydrogen gas generation and release of fission products. In this paper, the thermal characteristics of a channel for Indian PHWR under critical break failure is studied using experimental and numerical techniques. The experiment is carried out on an Indian PHWR having a fuel bundle of 37-fuel elements. The temperature profiles for different parts of the simulated channel comprising of fuel pins, PT and CT are obtained under steady condition. The numerical analysis is also performed using ANSYS Fluent 19.0. From the study, it is found that there is a significant radial temperature gradient in the fuel bundle from the center ring to the outer ring. Also, no significant circumferential temperature gradient is observed in the fuel bundle, PT and CT.